The comparative study of judicial activism in Malaysia and India / Mohamad Muhaimin Zakaria … [et al.] - Zakaria, Mohamad Muhaimin; Nazeri, Abdul Khaliq; Abdullah, Muhamad Atif; Zuber, Mohamad Afiq (Faculty of Law, 2013)
This research was conducted to find out whether the practice of judicial activism is possible in Malaysia. The reason why this topic was chosen is due to the fact that each judgments made by judges are unique in its own way. From this research we are able to see that certain judges apply strict interpretation of the law while some inserted a hint of creativity in making a decision. Besides that, we are able to identify the advantages of applying judicial activism and also the implications of improper practice and over practice of judicial activism. India was chosen as a benchmark for our research because of its practice of judicial activism that is a few decades more advanced than Malaysia and has more legal occurrences that can be compared with Malaysia. Besides that, from the resources that we have gathered, we have seen that the judges in India have actively participated injudicial activism to the extent that they also get involved in law making process. This research was conducted by way of perusing the decided cases and articles written by various academicians, lawyers and judges. Besides that, we also attained our sources by conducting interviews with the judges from the Court of Appeal and the High Court. From this research, we have managed to identify the benefits of judicial activism and its effects. Besides that, we have managed to create a simple guideline that can be referred in practicing judicial activism.